The effect of spatial configuration in the thermal area of Fort Oranje public space in Ternate City - Muhammad, Asri A.; Marasabessy, Firdawaty; Kusumawanto, Arif; Nareswari, Ardhya (Journal of Architecture and Urbanism, 2017)
Crowded city will be impact to the temperature of urban areas. This condition is commonly known as the urban heat island effect. It’s impact to the activity that happened in the urban space. Recently, Fort Oranje (urban space/square) that has history value has been revitalized as an urban public space that is crowd visited by Ternate’s people. Therefore, the thermal comfort becomes an important thing and that is available to the users. The research is aim to know the influence of space configuration change to the aspect of thermal comfort in the urban public space. The method that is used in this research is empirical measurement and simulation method using Envi-MET software. This method is used to simulate the condition of thermal area in Fort Oranje. The result of this research showed that space configuration that change before and after the development of Ternate waterfront city impact to the thermal conditions in Fort Oranje public space.